Three-dimensional evaluation of alveolar bone thickness of mandibular anterior teeth in different dentofacial types - (:unkn) unknown (MEDKNOW PUBLICATIONS & MEDIA PVT LTD, 2018)
Aim: The aim of this randomized study was to compare the alveolar bone thickness (ABT) of the mandibular incisor teeth of dental and skeletal Class I, II, and III adult patients at labial and lingual aspects of the bone and develop recommendations for the associated movements of teeth in this region, taking vertical facial type into consideration. Material and Methods: Sixty-two Class I, 74 Class II, and 63 Class III patients - aged between 20 and 45 - were assigned to three subgroups u high (H), low (L), and normal (N) growth patterns. On the axial slices of computerized tomographies, the measurements for the ABT on labial and lingual sides of the mandibular incisors were carried out at three levels. Results: In Class I group, at apex region, ABT of subgroups N and L were greater than H, at labial side. In Class II, ABT of subgroups N and L were greater than H, at apex at both sides and cervical lingual region. Similarly, ABT of subgroup L of Class III group was greater than H, at labial and lingual apex, mid-root regions. In Class II, the ABT of subgroup H was greater than L, at lingual cementoenamel junction. Conclusions: ABT of mandibular incisors of Class I patients is not affected from vertical pattern except for apical region. There is not a thick bone on the lingual side of the Class II, high-angle patients. The ABT of the Class III, high-angle patients is thin as a risk factor for proclination.
Keywords: Alveolar bone thickness; cone-beam computed tomography; lower incisors; BEAM COMPUTED-TOMOGRAPHY; TOOTH MOVEMENT; CLASS-I; PATTERNS; FENESTRATION; PROGNATHISM; DEHISCENCE; SYMPHYSIS; IMPLANTS; GROWTH